2011
DOI: 10.1016/j.jacc.2011.05.051
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Contractile Function Following a Successful Modified Maze Procedure at Surgery and the Risk for Subsequent Thromboembolic Stroke

Abstract: Absence of LA contraction and LA volume index ≥33 ml/m(2) result in a significant increase in the risk for thromboembolic stroke after the Maze procedure for patients in sinus rhythm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 18 publications
4
60
2
Order By: Relevance
“…The role of the LAA has been clouded by small numbers of patients and the continuation of anticoagulation in a minority of postoperative patients, as well as a retrospective series suggesting a persistent stroke risk in postoperative patients who are in sinus rhythm, with large atria, and poor atrial contraction leading to effective LA asystole. 1312 …”
Section: Section 12: Surgical and Hybrid Af Ablationmentioning
confidence: 99%
“…The role of the LAA has been clouded by small numbers of patients and the continuation of anticoagulation in a minority of postoperative patients, as well as a retrospective series suggesting a persistent stroke risk in postoperative patients who are in sinus rhythm, with large atria, and poor atrial contraction leading to effective LA asystole. 1312 …”
Section: Section 12: Surgical and Hybrid Af Ablationmentioning
confidence: 99%
“…The recovery of LA activity may also contribute to the prevention of AF-related stroke or thromboembolism 18,19 by increasing the blood flow velocity in the LA. 20 According to a recent study by Buber et al, 47 (31%) of 150 patients with recovered SR after the maze operation showed no evidence of LA mechanical contraction at 3-month follow-up echocardiography and the absence of LA contraction resulted in a significant increase in the risk for thromboembolic stroke in patients with SR. 21 In our data incorporating only cryo-maze cases to ensure homogeneity of the study population, lack of LA activity was also associated with an increased risk of thromboembolic stroke in the univariate analysis. However, the significant association was not maintained in the multivariate analysis.…”
Section: Effect Of La Activity On Long-term Outcomesmentioning
confidence: 76%
“…Multivariate analysis demonstrated that the lack of LAMF was associated with a 5-fold increase in the risk for stroke (P=0.02). 16 The current case study involves a patient whom underwent pulmonary vein isolation, and the Cox maze III procedure, as well, and had a marked absence of LAMF postoperatively. This case illustrates the importance of evaluating LAMF after the Cox maze procedure or pulmonary vein isolation to determine the length of anticoagulation needed to prevent thromboembolic sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…An investigation of 150 patients who underwent either radiofrequency or cryoablation maze procedures revealed that, at a mean follow-up of 24.5 months, 47 (31%) patients lacked LAMF. 16 Moreover, lack of LAMF was associated with a 5-fold increase in the risk of stroke (P=0.02). 16 The absence of LAMF after the Cox maze III procedure is as high as 39% 17 and has been demonstrated to persist up to 56 months.…”
Section: Patient Presentation (Continued)mentioning
confidence: 97%
See 1 more Smart Citation